A Compact Quasi-Yagi Antenna with High Gain by Employing the Bent Arms and Split-Ring Resonators - Wen-Ying Zhou; Zhong-Lei Mei; Mai Lu (International Journal of Antennas and Propagation)
A compact quasi-Yagi antenna with bent arms and split-ring resonators (SRRs) is proposed. Compared with traditional quasi-Yagi antennas employing straight arms, the resonant frequency of the proposed antenna could be always consistent with its center frequency, and there is no obvious frequency shift under the process of its miniaturization. The SRRs are adopted in the proposed compact antenna for a high gain of 6.58 dBi. The reliability verification of the proposed antenna radiation characteristics is further experimentally proved with the prototype measurement. The proposed quasi-Yagi antenna has an adjustable compact structure and low frequency offset and could be used in the precise point-to-point wireless communication environment.